1979
DOI: 10.1136/ard.38.5.471
|View full text |Cite
|
Sign up to set email alerts
|

Patients' expectations in relation to outcome of total hip replacment surgery.

Abstract: SUMMARY The importance of expectations has been assessed by giving 88 patients who had undergone total hip replacement surgery a series of visual analogue scales to provide a pain score, a 5-point rating scale to assess their remembered expectations, and an interview to establish clinical, functional, social, and psychological data. Patients generally had high expectations, but only 55 % had their expectations fulfilled. Despite this, 86% claimed the operation to be successful, though when questioned more clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0
4

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 6 publications
(5 reference statements)
3
58
0
4
Order By: Relevance
“…Burton et al showed that in the case of a specific intervention (total hip replacement), dissatisfaction with outcome correlated with failure to fulfill prior expectations [6]. In our study, expectations relate to the further progress of the disease without specific therapeutic intervention.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Burton et al showed that in the case of a specific intervention (total hip replacement), dissatisfaction with outcome correlated with failure to fulfill prior expectations [6]. In our study, expectations relate to the further progress of the disease without specific therapeutic intervention.…”
Section: Discussionmentioning
confidence: 57%
“…These correlations are relatively low, however, with actual disability explaining only 48% of the variance in dissatisfaction with disability. Other work has suggested that dissatisfaction with the outcome of total hip replacement relates to prior expectation [6] and that depression influences dissatisfaction with disability in the chronically ill [7].…”
mentioning
confidence: 99%
“…Similar to what has been reported in Journal of Surgical Oncology Defined as patients having an incomplete primary excision at a peripheral hospital prior to their definitive surgery at a study center. other surgical populations, patients' expectations were generally high, with almost 50% of our cohort expecting a short, uncomplicated recovery and no difficulty performing daily activities post-operatively [19,28,29,33,34]. However, we also found that a significant percentage of our patients did not know what to expect regarding their postoperative recovery.…”
Section: Discussionmentioning
confidence: 67%
“…The design of this investigation was modeled after prior surveys that assessed expectations for other common orthopaedic conditions [5,10,16,19,[21][22][23][24]. The study was a prospective cohort validation study and was performed in the clinical practices of four different orthopaedic hand surgeons in one institution.…”
Section: Methodsmentioning
confidence: 99%